Some Certain Fuzzy Fractional Inequalities for Up and Down ℏ-Pre-Invex via Fuzzy-Number Valued Mappings - Muhammad Bilal Khan; Adriana Catas; Najla Aloraini; Mohamed S. Soliman (Fractal and Fractional, 2023)
In this study, we apply a recently developed idea of up and down fuzzy-ordered relations between two fuzzy numbers. Here, we consider fuzzy Riemann–Liouville fractional integrals to establish the Hermite–Hadamard-, Fejér-, and Pachpatte-type inequalities. We estimate fuzzy fractional inequalities for a newly introduced class of ℏ-preinvexity over fuzzy-number valued settings. For the first time, such inequalities involving up and down fuzzy-ordered functions are proven using the fuzzy fractional operator. The stated inequalities are supported by a few numerical examples that will be helpful to validate our main results.